TIKTOK SEBAGAI DISTRAKSI, MEMPENGARUHI PRODUKTIVITAS DAN MANAJEMEN WAKTU PADA GENERASI Z: TIKTOK AS A DISTRACTION, AFFECTING PRODUCTIVITY AND TIME MANAGEMENT IN GENERATION Z - Nadya Gracia Saragi; Firman; Sahiruddin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid development of information and communication technology has transformed the behavioral patterns of Generation Z, particularly in their use of social media such as TikTok. While TikTok provides entertainment and creative expression, excessive use can lead to distraction that negatively affects students’ productivity and time management. This study aims to analyze the impact of TikTok as a distraction on productivity and time management among students of the Information Technology Education Study Program at Muhammadiyah University of Education, Sorong, while also examining the social influence of parents and peers. A quantitative descriptive-correlational approach was employed, involving 30 active TikTok users (minimum one hour per day). Data were collected using a closed-ended questionnaire measuring levels of distraction, productivity, time management, and social influence. Results showed that distraction, productivity, and time management were at a moderate level (mean = 2.83). Peer influence (mean = 3.08) was found to be stronger than parental influence (mean = 2.22) in shaping TikTok usage behavior. Pearson’s correlation analysis indicated a significant positive relationship (r = 0.554; p < 0.01) between distraction, time management difficulties, and social factors. These findings highlight the importance of digital literacy programs emphasizing effective time management and healthy social media habits through peer-to-peer learning approaches.